Optimalisasi Pengembangan Desa Wisata Kampung Sawah di Desa Talagasari Kecamatan Kawali Kabupaten Ciamis - Ranti Lestari; Ujang Irman Saputra; Riris Risnawati; Yusmaida Nur Afrita (International Forum of Researchers and Lecturers, 2025)
This study aims to provide an understanding of the optimization of the development of the Kampung Sawah tourist village which focuses on tourism trends that provide direct benefits to local communities, the role of villages in the local economy, making tourist villages based on sustainable tourism, the implementation of tourism pentahelix and digitalization ecosystems at the Kampung Sawah tourist attraction in Talagasari Village, Kawali District, Ciamis Regency. The methods used include the case study approach method. The activity mechanism consists of several stages, namely field surveys and data analysis. This activity begins with direct observation, interviews and identification of problems with related parties in Talagasari Village. The results of this service show that the managers of tourist attractions are able to try to re-operate the Kampung Sawah tourist attraction, this will be discussed again and evaluated together with the village government, Village Community Institutions and the Community.